Insulin analogues versus human insulin in type 1 diabetes: direct and indirect meta-analyses of efficacy and safety - Andréia Cristina Conegero Sanches; Cassyano Januário Correr; Rafael Venson; Patrícia Rodrigues Gonçalves; Mariana Martins Garcia; Mário Sérgio Piantavini; Roberto Pontarolo (Universidade de São Paulo, 2013)
All patients with Diabetes Mellitus (DM) receive insulin therapy. In this study, we evaluated the efficacy, safety and tolerability of human insulin and insulin analogues. We performed a systematic review of the literature and a meta-analysis according to the Cochrane Collaboration methodology. In the absence of clinical studies comparing insulins, we performed a mixed treatment comparison to establish the differences between the active treatments. We included studies published from 1995 to 2010. HbA1c results, episodes of hypoglycemia and nocturnal hypoglycemia data were extracted and analyzed. Thirty-five randomized clinical trials were selected after examining the abstract and a full text review. These studies included 4,206 patients who received long-acting insulin analogues and 5,733 patients who received short-acting insulin analogues. Pooled data regarding efficacy indicated no significant differences in HbA1c values between glargine or detemir (once daily) and NPH insulin. However, a twice-daily dose of detemir produced differences in HbA1c values that favored detemir (-0.14% [95% CI: -0.21 to -0.08]; p<0.0001; I²=0%). Direct and indirect comparisons are consistent and show that there were no significant differences between human insulin and insulin analogues in efficacy or safety. Our results indicate that long- and short-acting insulin analogues offer few clinical advantages over conventional human insulin.